Warriors: Warrior's return / 3 - Hunter, Erin; Barry, James L., 1979- (Warriors [manga, 2008)
Graystripe and Millie finally locate the ThunderClan's old territory only to discover the forest devastated by Twolegs, but they continue searching for remaining Clan members, following a path pointed out to them by an old friend, even though Graystripe worries their quest is hopeless.